Analysis Student Understanding Stage in Using Learning Media Apps Canva - Meisyi, Riska; Arisma, Nuria; Wahyuni, Riska Putri; Iskandar, M. Yakub; Samsurizal, Samsurizal (Al-Hashif: Jurnal Pendidikan dan Pendidikan Islam, 2023)
Education today is education in the era of the 21st century. Learning must develop critical thinking and problem-solving skills, creativity and innovation, communication, and collaboration. Therefore, teachers must be creative and innovative in creating learning that fosters high-level thinking in students. One of them is choosing varied and digital-based learning media for educational development. This research aims to describe innovative and creative digital-based learning media, namely in the form of learning videos using the Canva application in learning flat-shaped mathematics. Learning videos using the Canva application in flat mathematics learning is one of the right solutions to support teachers in developing digital-based learning media. The type of research carried out was descriptive research with a literature study. The research subject is the author as key informant and the research object or research target is articles related to using the Canva application in learning activities. The data collection method used in this research is the documentation method with instruments in printed text soft files or articles. The results of this research show that learning videos using the Canva application in learning mathematics is an interesting and innovative learning media by educational developments in this century. The development of learning media in the form of videos through the Canva application has become a reference for innovative learning media by utilizing effective and efficient digital-based applications in line with 21st-century developments.